2017
DOI: 10.14302/issn.2574-612x.ijpr-17-1746
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in psycho-oncological care among Turkish immigrant women with breast cancer in Germany – an interview study

Abstract: I n t e r n a t i o n a l J o u r n a l o f P s y c h o t h e r a p y P r a c t i c e a n d R e s e a r c h ISSN NO: 2576-612X Research Article Deficits in Psycho- Methods:In this qualitative study semi-structured face to face interviews were conducted with Turkish breast cancer patients in Germany. Interviews were transcribed and analyzed in Turkish by two Turkish speaking researchers via content analysis using MAXQDA qualitative analysis software (version 11). Results were discussed among a bilingual researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
(11 reference statements)
0
4
0
2
Order By: Relevance
“…PMB had more need for (psychological) support and expected better results from treatment and rehabilitation than non-PMB did. This was identified for Turkish PMB [13,34,50,59,58] in particular. Kessemeier et al (2019) found in their cohort study that PMB were less satisfied with rehabilitation services [50].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…PMB had more need for (psychological) support and expected better results from treatment and rehabilitation than non-PMB did. This was identified for Turkish PMB [13,34,50,59,58] in particular. Kessemeier et al (2019) found in their cohort study that PMB were less satisfied with rehabilitation services [50].…”
Section: Resultsmentioning
confidence: 91%
“… Schröder et al 2020 [ 57 ] x x x x d,i 24. Yilmaz-Aslan et al 2017 [ 58 ] [ 59 ] x x x c x x 25. Zollmann et al 2016 [ 60 ] x x x d a d descriptive analysis, i inductive analysis, c content analysis b Personal Communication with Aksakal and Yilmaz-Aslan (March 2020) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To what extent these structures are adequate from the patients’ perspective has to be subject to further research. There are indications that the support needs of specific groups of patients with breast cancer, for example, patients with an immigration background,12 patients with comorbidities,13 patients receiving neoadjuvant chemotherapy or showing passive-resigning coping skills,14 patients who are offered individualised treatment approaches based on molecular genetic methods,15 male patients with breast cancer, or patients’ partners or caregivers,16 17 have not yet been addressed adequately. Should subsequent studies reveal that disease-specific, treatment-related or target group-specific needs are not fully met, it will be necessary to examine the institutional determinants in order to derive specific measures for the underserved patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Die drei zugrundeliegenden Leitfäden orientierten sich dabei am Verlauf der Rehabilitation. Sie enthielten verschiedene Themenbereiche, in die neben Ergebnissen aus früheren Studien 10 20 auch Inhalte des Fragebogens zu rehabilitationsbezogenen Erwartungen und Motivation (FREM-17) 21 einflossen. Rehabilitand*innen wurden zu den o.g.…”
Section: Methodenunclassified